The evolution of vimentin and desmin in Pectoralis major muscles of broiler chickens supports their essential role in muscle regeneration - Soglia, Francesca; Bordini, Martina; Mazzoni, Maurizio; Zappaterra, Martina; Di Nunzio, Mattia; Clavenzani, Paolo; Davoli, Roberta; Meluzzi, Adele; Sirri, Federico; Petracci, Massimiliano (Frontiers in Physiology, 2022)
Vimentin (VIM) and desmin (DES) are muscle-specific proteins having crucial roles in maintaining the lateral organization and alignment of the sarcomeric structure during myofibrils’ regeneration. The present experiment was designed to ascertain the evolution of VIM and DES in Pectoralis major muscles (PM) of fast-growing (FG) and medium-growing (MG) meat-type chickens both at the protein and gene levels. MG broilers were considered as a control group whereas the evolution of VIM and DES over the growth period was evaluated in FG by collecting samples at different developmental stages (7, 14, 21, 28, 35, and 42 d). After performing a preliminary classification of the samples based on their histological features, 5 PM/sampling time/genotype were selected for western blot, immunohistochemistry (IHC), and gene expression analyses. Overall, the findings obtained at the protein level mirrored those related to their encoding genes, although a potential time lag required to observe the consequences of gene expression was evident. The 2- and 3-fold higher level of the VIM-based heterodimer observed in FG at d 21 and d 28 in comparison with MG of the same age might be ascribed to the beginning and progressive development of the regenerative processes. This hypothesis is supported by IHC highlighting the presence of fibers to co-expressing VIM and DES. In addition, gene expression analyses suggested that, unlike VIM common sequence, VIM long isoform may not be directly implicated in muscle regeneration. As for DES content, the fluctuating trends observed for both the native protein and its heterodimer in FG might be ascribed to its importance for maintaining the structural organization of the regenerating fibers. Furthermore, the higher expression level of the DES gene in FG in comparison with MG further supported its potential application as a marker of muscle fibers’ regeneration. In conclusion, the findings of the present research seem to support the existence of a relationship between the occurrence of muscle regeneration and the growth rate of meat-type chickens and corroborate the potential use of VIM and DES as molecular markers of these cellular processes.